DAMPAK EFEKTIVITAS, AKUNTABILITAS, TRANSPARANSI, DAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DANA DESA TERHADAP PEMBANGUNAN DESA - Sari, Cindi Pradita; Firdaus, Muhammad; Widaninggar, Nanda (Growth, 2024)
This study aims to examine the effect of effectiveness, accountability, transparency and community participation in the management of village funds on development in Tanjungrejo Village, Wuluhan District. This study used a questionnaire distribution method with a purposive sampling technique. The analysis used is multiple linear regression. The population of this study was the Village Head, Village Officials, RT and RW, Community Institutions and the people of Tanjungrejo Village, Wuluhan District. The results of this study indicate that partially the effectiveness and accountability variables in the management of village funds have no effect on village development. The variables of transparency and community participation in the management of village funds partially affect village development. Simultaneously, the variables of effectiveness, accountability, transparency and community participation in the management of village funds have an effect on village development.